Multilayer Film

JP7668805B2Active Publication Date: 2025-04-253M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022545985
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-29
Filing Date
2021-01-25
Publication Date
2025-04-25
Estimated Expiration
2041-01-25

AI Technical Summary

Technical Problem

Conventional multilayer optical films face challenges in achieving high transmittance and low haze while maintaining mechanical properties, as blending polymers to improve flexibility often adversely affects optical properties due to immiscibility issues.

Method used

The use of nanocomposite layers comprising a polymer matrix with surface-modified metal oxide nanoparticles, such as silica, dispersed in a polymer blend with (meth)acrylic acid monomer units, enhances mechanical properties and maintains optical clarity by preventing nanoparticle agglomeration.

Benefits of technology

The solution achieves high transmittance and low haze, along with improved mechanical properties like impact resistance and tensile modulus, making the films suitable for applications requiring both optical clarity and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000055_0000
    Figure 00000055_0000
  • Figure 00000056_0000
    Figure 00000056_0000
  • Figure 00000057_0000
    Figure 00000057_0000
Patent Text Reader

Abstract

The multilayer film includes a plurality of first layers and a plurality of polymeric second layers arranged along the thickness direction of the multilayer film. The first and second layers have different compositions. At least one layer of the multilayer film includes at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer. The at least one polymer includes a first polymer including (meth)acrylic acid monomer units. The metal oxide nanoparticles are surface-modified with a carboxylic acid silane surface modifier.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Multi-layer window films can be applied to window glass to increase shatter resistance.

[0002] Multilayer optical films can reflect light through optical interference. Summary of the Invention

[0003] The present disclosure generally relates to multilayer films. The multilayer film may be a window film adapted to bond to glass to increase the shatter resistance and safety of the glass, and / or the multilayer film may be a multilayer optical film that reflects light of at least one polarization state within at least one wavelength range. Multilayer films typically include at least one nanocomposite layer and at least one other layer. The nanocomposite layer includes at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer. The at least one polymer includes a first polymer including (meth)acrylic acid monomer units. The at least one polymer may further include a second polymer blended with the first polymer. In some embodiments, the nanocomposite layer is replaced with a layer of at least one polymer (e.g., a suitable blend of the first and second polymers that does not include metal oxide nanoparticles). The metal oxide nanoparticles are surface-modified with a carboxylic acid silane surface modifier. The nanocomposite layer of the multilayer film may be a transparent elastomeric nanocomposite layer. In some embodiments, the nanocomposites described herein can have high transmittance and low haze up to very high nanoparticle loadings. In some embodiments, the nanocomposites also exhibit improved mechanical properties, such as improved impact resistance and / or tensile modulus.

[0004] In some embodiments, a multilayer film is provided that includes a plurality of first layers and a polymer second layer arranged along the thickness direction of the multilayer film. The first and second layers have different compositions. Each of the first layers includes at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer. The at least one polymer includes a first polymer that includes (meth)acrylic acid monomer units. The metal oxide nanoparticles are represented by Formula 1: [ka] [In the formula, R1 is C1~C 10 is an alkoxy group, R2 and R3 are independently C1 to C 10 Alkyl groups and C1-C 10 alkoxy groups; A is C1~C 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 wherein the linker group is selected from the group consisting of amide-containing groups.

[0005] In some embodiments, a multilayer film is provided that includes a first layer and a plurality of alternating polymer layers disposed on the first layer. The first layer includes at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer. The at least one polymer includes a first polymer that includes (meth)acrylic acid monomer units. The metal oxide nanoparticles are surface-modified with a surface modifier that includes a carboxylic acid silane of Formula 1:

[0006] These and other aspects will become apparent from the following detailed description. In no event, however, should this brief summary be construed as limiting the claimed subject matter. [Brief explanation of the drawings]

[0007] [Figure 1] FIG. 1 is a schematic side view of an exemplary multilayer film according to some embodiments of the present disclosure. [Figure 2] FIG. 1 is a schematic side view of an exemplary multilayer film according to some embodiments of the present disclosure. [Figure 3] FIG. 1 is a schematic side view of an exemplary multilayer film according to some embodiments of the present disclosure. [Figure 4] FIG. 1 is a schematic side view of an exemplary multilayer film according to some embodiments of the present disclosure. [Figure 5] 1 is a schematic diagram of light incident substantially normally on a film; [Figure 6] 1 is a schematic plot of transmittance versus wavelength for a multilayer film according to some embodiments. [Figure 7] 1 is a schematic cross-sectional view of an exemplary nanocomposite layer. DETAILED DESCRIPTION OF THE INVENTION

[0008] In the following description, reference is made to the accompanying drawings that form a part hereof, and in which are shown by way of illustration various embodiments. The drawings are not necessarily to scale. It is to be understood that other embodiments are contemplated and may be made without departing from the scope or spirit of the specification. Accordingly, the following detailed description is not to be taken in a limiting sense.

[0009] Disclosed herein is a multilayer film, wherein at least one layer of the film comprises a nanocomposite described herein. The multilayer film can be a window film adapted to bond to glass to increase the shatter resistance of the glass, and / or the multilayer film can be a multilayer optical film that reflects light of at least one polarization state within at least one wavelength range.

[0010] Multilayer films, according to some embodiments, can be used, for example, in architectural or vehicle applications. For example, architectural window films can be or include a windproof film bonded to window glass (e.g., on the inner glass surface, the outer glass surface, or between glass layers) for mechanical protection (e.g., shatter resistance), and can optionally also include an infrared solar blocking film. In vehicle (e.g., automotive) applications, multilayer films can be disposed between layers of windshield glass for one or more of mechanical properties, infrared reflection, or reflection of projected head-up display images, as further described elsewhere herein. Multilayer films can also be used as reflectors in automotive or other applications. Multilayer films for other applications, according to some embodiments, include, for example, device-hiding reflective films that can be used to create camouflage effects that reduce the visual impact of cellular antennas or other structures.

[0011] The nanocomposites described herein typically include an ionic elastomer. The use of an ionomeric elastomer in the outer layer of a multilayer film can, for example, improve bonding of the film to glass or other surfaces, allowing the multilayer film to be directly bonded to glass (e.g., a window or windshield).

[0012] Multilayer films are often formed by coextrusion of multiple layers, followed in some cases by stretching the film to orient some of the layers. The nanocomposites described herein typically contain an ionic elastomer and nanoparticles dispersed in the ionic elastomer. The nanoparticles can be used to modify the melt rheology (e.g., melt flow index) for coextrusion with other layers of the multilayer film. Alternatively, or in addition, blends of ionomers (e.g., two-monomer unit copolymers and terpolymers) can be used to at least partially modify the melt rheology for coextrusion with other layers of the multilayer film, depending on the polymer of the blend.

[0013] An alternative to a nanocomposite layer is a layer formed from at least one polymer described herein (e.g., a blend of two or more ionomers), according to some embodiments. Nanocomposites or ionomer blends, according to some embodiments, provide improved tear resistance in window films and / or multilayer optical films.

[0014] Multilayer optical films are described, for example, in U.S. Patent Nos. 5,882,774 (Jonza et al.), 6,179,948 (Merrill et al.), and 6,498,683 (Condo et al.). Multilayer optical films can be tailored to provide desired reflections over a given wavelength range for a given polarization state by appropriately selecting the layer materials for their refractive indices and adjusting the layer thicknesses, as is known in the art.

[0015] In some embodiments, the multilayer films described herein can be visible light mirror films (e.g., having an average reflectance of at least 70% over a wavelength range extending from 450 nm to 650 nm for unpolarized light at substantially normal incidence), infrared mirror films (e.g., having an average reflectance of at least 70% over a wavelength range extending from 800 nm to 900 nm, or from 900 nm to 1000 nm for unpolarized light at substantially normal incidence), reflective polarizers (e.g., having an average reflectance that is at least 20%, or at least 30%, higher for a first polarization state over a wavelength range extending from 450 nm to 650 nm than for a second polarization state that is orthogonal to light at substantially normal incidence), or notch optical filters. The notch optical filter can be, for example, a notch mirror (e.g., having an average reflectivity of at least 70% over at least one wavelength range that is at least 5 nm wide and no more than about 100 nm wide for light in an unpolarized state at substantially normal incidence), or a notch reflective polarizer (e.g., having an average reflectivity that is at least 30% higher over at least one wavelength range that is at least 5 nm wide and no more than about 100 nm wide for a first polarization state than for a second polarization state that is orthogonal to light at substantially normal incidence), or the notch optical filter can have a notch transmission band for at least one polarization state.

[0016] Multilayer films can be used in liquid crystal display panels, for example, as back reflectors in backlights or as reflective polarizers between the backlight and the liquid crystal display. As another example, multilayer films can be incorporated between glass layers in an automobile windshield to reflect projected head-up display images to the viewer. In such cases, the multilayer film is typically a reflective polarizer (e.g., having an average reflectance of about 30 to about 70% for substantially normally incident visible light in a block polarization state and an average reflectance of less than about 10% for substantially normally incident visible light in a pass polarization state; such multilayer films are described, for example, in U.S. Pat. No. 6,952,312 (Weber et al.) and WO 2019 / 145860 (Haag et al.)).

[0017] Multilayer window films and / or tear-resistant films are described, for example, in U.S. Patent Nos. 5,604,019 (Bland et al.), 6,040,061 (Bland et al.), and 9,776,381 (Liu et al.). In some cases, such films include layers that are oriented and / or rigid and layers that are substantially isotropic and / or malleable. The combination of layers with different mechanical properties can result in improved tear resistance and / or improved shatter resistance of the films in a stack, including the film disposed on glass.

[0018] In some embodiments, the multilayer films described herein are multilayer window films adapted to increase the shatter resistance of window panes. In some embodiments, the multilayer films of the present disclosure include multilayer window films for shatter resistance and multilayer optical films for reducing solar heating (e.g., infrared mirror films). The window film and multilayer optical film can be integrally formed (e.g., coextruded together) or can be formed separately and bonded, for example, with an adhesive layer.

[0019] In some embodiments, at least one layer of a multilayer film (e.g., a skin layer or protective boundary layer of a multilayer optical film, and / or a low refractive index layer of a multilayer optical film, and / or a malleable layer of a tear resistant film or window film) comprises a nanocomposite of the present disclosure or comprises an ionomer blend of the present disclosure.

[0020] Conventional ionic elastomers have some desirable properties, such as high visible transmittance and low haze, chemical resistance, and flexibility. However, conventional ionic elastomeric polymers lack, for example, the mechanical characteristics or tensile modulus that are desirable for some applications.

[0021] Particulate fillers have been incorporated into polymers to improve their mechanical properties. However, the majority of commercially available filled polymers are opaque and therefore unsuitable for use in optical articles. In addition, rigid particulate fillers can adversely affect the flexibility of the polymers they are combined with.

[0022] One technique for providing modified properties is to blend polymer materials. This approach can be problematic because preparing a blend to improve one property, such as flexibility, can adversely affect other properties, such as optical properties. This is particularly true for optical properties, since the majority of polymer blends have at least some degree of immiscibility. Lack of miscibility can dramatically affect optical properties such as visible light transmittance, haze, and transparency. Even polymers with the same or similar monomer composition can be immiscible if, for example, the polymers have different degrees of branching. Therefore, modifying a polymer composition by blending it with another polymer, even if the polymers appear similar, is not straightforward, especially if the blended composition has desired optical properties. It has been unexpectedly discovered that blends of different polymers containing similar contents of (meth)acrylic acid monomer units provide improved mechanical properties while maintaining desired optical properties (e.g., high light transmittance and / or low optical haze).

[0023] The terms "miscible" or "miscibility" refer to at least two polymers that are compatible with each other such that a blend of the at least two polymers does not phase separate to form phase-separated microdomains large enough to produce significant scattering of visible light (wavelengths of about 400 to about 700 nm).

[0024] The terms "immiscible" or "immiscibility" refer to at least two polymers that are incompatible with each other such that a blend of the at least two polymers phase separates to form phase-separated microdomains large enough to produce significant scattering of visible light (wavelengths of about 400 to about 700 nm), resulting in unacceptable haze.

[0025] The multilayer films of the present disclosure, according to some preferred embodiments, achieve the conflicting goals of flexibility, optical performance (e.g., desired transparency or reflectivity), and improved mechanical properties. The nanocomposite layer of the multilayer film typically comprises a polymer matrix and a surface-modified nanoparticle filler. The polymer matrix, which may also be referred to as the polymer phase, comprises at least one polymer (e.g., a polymer or a blend of polymers).

[0026] The nanocomposite layers of the present disclosure utilize metal oxide nanoparticles, which are particles with an average diameter in the nanometer range. These particles provide improved mechanical properties to the nanocomposite, and due to their small size, according to some embodiments, the nanoparticles do not appreciably scatter visible light. The nanoparticles can be surface-modified to achieve compatibility with at least one polymer and avoid weak or strong agglomeration of the nanoparticles in the nanocomposite, which can lead to poor optical properties. The surface modifier is typically a carboxylic acid-functional silane. Without being bound by theory, it is believed that the acid functionality on the surface modifier improves compatibility between the particles and the acid-functional (meth)acrylic polymer of the at least one polymer. Some of the acid functionality on the surface-modified nanoparticles may be neutralized, as may at least some of the acid functionality on the (meth)acrylic polymer. The acid functionality in the surface modifier favors the dispersibility of the nanoparticles in water. When added to a basic surface-unmodified nanoparticle solution (e.g., NALCO 2327), the acid groups of the acid silane are at least partially neutralized, making the silane soluble in the aqueous phase so that the surface of the silica can be easily modified. Furthermore, it has been found that the acid silane on the surface of the particle leads to excellent compatibility of the nanoparticles in the host polymer matrix in coating and melt processing of ionic elastomeric nanocomposite materials, which can enable interaction of the nanoparticles with the ionic groups of the elastomeric ionomeric polymer.

[0027] FIG. 1 is a schematic cross-sectional view of a multilayer film 100 including a plurality of first layers 110 and second layers 120 arranged along the thickness direction (z-direction) of the multilayer film 100. Each of the first and second layers 110 and 120 extends along orthogonal first and second directions (x- and y-directions). The thickness direction is orthogonal to the first and second directions. The first and second layers can be arranged sequentially in any suitable manner. In the illustrated embodiment, the first and second layers 110 and 120 alternate along the thickness direction. In other embodiments, the first and second layers can be arranged in a non-alternating order.

[0028] In some embodiments, each of the first layers 110 is a nanocomposite layer, as further described elsewhere herein. In some embodiments, each of the second layers 120 is a polymer layer. Suitable materials for the second layer 120 include, for example, polyethylene naphthalate (PEN), polyethylene terephthalate (PET), or copolymers or blends thereof. Other suitable materials for the second layer 120 include, for example, polycarbonate, polyacrylate, and naphthalate, as well as other polyesters, including terephthalate-containing polymers, such as polybutylene naphthalate (PBN), polypropylene naphthalate (PPN), polybutylene terephthalate (PBT), and polypropylene terephthalate (PPT), and blends or copolymers of any of the above with each other or with non-polyester polymers. Other suitable materials are described, for example, in U.S. Pat. Nos. 6,498,683 (Condo et al.) and 8,168,302 (Hebrink et al.). In some embodiments, each second layer 120 comprises a polyester comprising terephthalate monomer units and ethylene glycol monomer units.

[0029] Multilayer film 100 or other multilayer films described herein can be substantially planar, as shown generally in FIG. 1, or can be curved into a desired shape, for example, by thermoforming.

[0030] 2 is a schematic cross-sectional view of a multilayer film 200 including a plurality of first layers 110 and second layers 120 arranged along the thickness direction (z-direction) of the multilayer film 200. The multilayer film 200 may further include at least one third layer 130.

[0031] In some embodiments, the multilayer film 200 includes a plurality of third layers 130 of polymer disposed along the thickness direction along with the first and second layers 110 and 120 .

[0032] In some embodiments, the multilayer films 100 and / or 200 are window films adapted to increase the shatter resistance of glass. In some embodiments, the multilayer films have a light transmittance of at least 70 percent, or at least 80 percent, or at least 90 percent for unpolarized light at substantially normal incidence. Light transmittance can be determined in accordance with ASTM D1003-00, "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics." The term "light / luminous" refers to a wavelength-weighted average according to the spectral luminous efficiency function V() established by the Commission Internationale de l'Eclairage (CIE, 1987).

[0033] The multilayer films 100 and 200 may have more layers than are shown. In some embodiments, the multilayer films include 30 or fewer layers. For example, in some embodiments, the first and second layers total 4 to 30 layers, or 5 to 25 layers, or 5 to 20 layers. In some embodiments, a total of 5 layers are included, and the layer thicknesses are in the range of 20 micrometers to 100 micrometers, or 35 micrometers to 175 micrometers, or 50 micrometers to 250 micrometers. In some embodiments, a total of 7 layers are included, and the layer thicknesses are in the range of 20 micrometers to 140 micrometers, or 25 micrometers to 175 micrometers, or 30 micrometers to 210 micrometers. In some embodiments, a total of 13 layers are included, and the layer thicknesses are in the range of 10 micrometers to 130 micrometers, or 15 micrometers to 195 micrometers, or 20 micrometers to 260 micrometers.

[0034] In some embodiments, the multilayer film is adapted to transmit and reflect light primarily through optical interference. For example, layers 110 and 120 can be interference layers arranged in an optical repeating unit having an optical thickness selected to reflect desired wavelengths of light. As is known in the art, multilayer optical films comprising alternating layers can be used to provide desired reflection and transmission bands by appropriately selecting the layer materials for their refractive indices and layer thicknesses. Multilayer optical films and methods for making multilayer optical films are described, for example, in U.S. Patent Nos. 5,882,774 (Jonza et al.), 6,179,948 (Merrill et al.), 6,783,349 (Neavin et al.), 6,967,778 (Wheatley et al.), and 9,162,406 (Neavin et al.). A multilayer film, or an interference layer of a multilayer film, can be described as reflecting or transmitting light primarily through optical interference, and the reflectance and transmittance of the film or interference layer can be reasonably described by, or reasonably accurately modeled as resulting from, optical interference.

[0035] The interference layers are typically less than about 500 nm thick. In some embodiments, the first and second layers 110 and 120 each have an average thickness of less than 500 nm, or less than 400 nm, or less than 300 nm. In some embodiments, the first and second layers 110 and 120 each have an average thickness in the range of 10 nm to 200 nm, or 10 nm to 100 nm.

[0036] The number of layers can be fewer, more, or substantially more than that shown generally in Figures 1-2. For example, in some embodiments, the number of first and second layers totals at least 50. The total number of layers can be, for example, 50 to 1000, or 50 to 400, or 100 to 300. A higher number of layers may be desired, for example, to provide higher reflectivity and / or reflect over a broader wavelength range. In some embodiments, the multilayer optical film has a thickness in the range of, for example, 30 to 250 micrometers, or 50 to 200 micrometers.

[0037] In some embodiments, the first layer is substantially optically isotropic. For example, |nx-ny| and / or |nx-ny| of the first layer

number

number

[0038] In embodiments in which the low refractive index layer of a multilayer optical film comprises a nanocomposite layer herein, the average nanoparticle size can preferably range from 4 to 20 nm. Preferred nanoparticle sizes are such that the nanoparticles have an average diameter of less than half the thickness of the nanocomposite layer after the film is oriented. In some embodiments, the nanoparticles can be present in the nanocomposite layer in a range of, for example, 2% to 25%, 2% to 20%, or 2% to 15% by weight.

[0039] In some embodiments, the multilayer film includes a plurality of first and second layers that provide, for example, desired tear and / or shatter resistance properties, and further includes a plurality of alternating polymer layers disposed on the plurality of first and second layers. For example, the multilayer film of Figures 1-2 can provide the desired tear and / or shatter resistance properties, and can optionally further include a plurality of alternating polymer layers disposed on the illustrated layers to provide the desired reflectivity in the desired wavelength range.

[0040] 3 is a schematic cross-sectional view of an optical stack 301 including a multilayer film 300 disposed on a glass layer 350. The multilayer film 300 includes a plurality of first and second layers 110 and 120, and a plurality of alternating polymer layers 210 and 220 disposed on the plurality of first and second layers 110 and 120. In some embodiments, the multilayer film 300 is a window film, the glass layer 350 is a window pane, the plurality of alternating polymer layers 210 and 220 are adapted to reflect infrared light, and the plurality of first and second layers 110 and 120 are adapted to provide the glass layer 350 with desired shatter resistance.

[0041] An additional glass layer may be disposed on the plurality of alternating polymer layers 210 and 220 opposite layers 110 and 120. In some embodiments, the multilayer film further includes a plurality of additional layers (e.g., corresponding to layers 110 and 120) disposed between the additional glass layer and the alternating polymer layers 210 and 220. The additional layers may be included, for example, for enhanced shatter resistance. In some embodiments, the multilayer film 300 is disposed on or between glass layers for both strength (e.g., shatter resistance) and reflective properties (e.g., for head-up display and / or solar IR blocking). In other embodiments, the multilayer film (e.g., multilayer film 100 or 200 using optically thick layers) is disposed on or between glass layers primarily for strength. In other embodiments, the multilayer film (e.g., multilayer film 400 described elsewhere using interference layers) is disposed between glass layers primarily for reflective properties (e.g., for head-up display and / or solar IR blocking). In embodiments in which the multilayer film is disposed on or between glass layers, it is typically preferred that the layer of the multilayer film immediately adjacent to the glass layer comprises a nanocomposite or ionomer layer as described herein.

[0042] In some embodiments, at least first layer 110 comprises a nanocomposite of the present disclosure. In some embodiments, layers 210 and 220 and / or one of the optional skin layers or protective boundary layers (not shown in FIG. 3, see e.g., FIG. 4) formed with layers 210 and 220 comprise a nanocomposite of the present disclosure.

[0043] FIG. 4 is a schematic cross-sectional view of a multilayer film 400 including a first layer (any one of layers 140, 142, and 141 can be considered the first layer in the illustrated embodiment) and multiple alternating polymer layers 210 and 220 disposed on the first layer. In some embodiments, alternating polymer layers 210 and 220 have an average thickness of less than 500 nm or less than 400 nm. In some embodiments, layers 140, 142, and 144 each have a thickness of greater than 1 micrometer or greater than 2 micrometers. The first layer comprises a nanocomposite of the present disclosure. In some embodiments, two of layers 140, 142, and 141 comprise a nanocomposite of the present disclosure. In some embodiments, layers 140, 142, and 141 each comprise a nanocomposite of the present disclosure. Layers 140, 142, and 144 can be protective boundary layers or skin layers. As is known in the art, protective boundary layers can be added as outer layers of the packet of interference layers to protect the interference layers during processing of the film.

[0044] In some embodiments, the plurality of alternating polymer layers 210 and 220 comprises subgroups of alternating layers separated by one or more optically thick layers (e.g., an average thickness of greater than about 1 micrometer). In some embodiments, the multilayer film 400 comprises a first layer 140 and a second layer 142, with at least one subgroup 146 of alternating polymer layers disposed between the first and second layers 140 and 142. Alternatively, layer 142 can be omitted (e.g., there can be a single packet of alternating layers), and layer 144 can be considered a second layer having a plurality of alternating polymer layers disposed between the first and second layers.

[0045] The first layer comprises a nanocomposite of the present disclosure. For example, the first layer can comprise at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer, wherein the at least one polymer comprises a first polymer comprising (meth)acrylic acid monomer units, and the metal oxide nanoparticles are surface-modified with a carboxylic acid silane surface modifier (e.g., according to Formula 1 described elsewhere). In some embodiments, the at least one polymer further comprises a second polymer different from the first polymer blended with the first polymer, the second polymer comprising (meth)acrylic acid monomer units. In some embodiments, the second layer comprises at least one polymer, and the at least one polymer of the second layer comprises a first polymer comprising (meth)acrylic acid monomer units. In some embodiments, the second layer further comprises metal oxide nanoparticles dispersed in at least one polymer of the second layer, and the metal oxide nanoparticles of the second layer are surface-modified with a carboxylic acid silane surface modifier (e.g., according to Formula 1 described elsewhere). In some embodiments, at least one polymer of the second layer further comprises a second polymer different from the first polymer of the second layer blended with the first polymer of the second layer, wherein the second polymer of the second layer comprises (meth)acrylic acid monomer units.

[0046] In some embodiments, the alternating polymer layers include alternating first (210) and second (220) interference layers. Each first interference layer includes at least one polymer (e.g., a single polymer or a blend of first and second polymers), and at least one polymer in the first interference layer includes a polymer including (meth)acrylic acid monomer units. In some such embodiments, or in other embodiments, each second interference layer includes an oriented polyester. For example, each second interference layer can include a polyester including terephthalate monomer units and ethylene glycol monomer units. In some embodiments, the first layer 210 has less birefringence than the second layer 220. In some embodiments, the first layer 210 is substantially optically isotropic. In some embodiments, the first layer 210 is a low refractive index layer and the second layer 220 is a high refractive index layer.

[0047] In some embodiments, the nanocomposites described herein are used in layers where it is desired that the layer have a low refractive index and / or remain unoriented. For example, the nanocomposite can be used as a low refractive index layer when alternating high and low refractive index layers are used in a multilayer optical film. In some embodiments, the nanoparticles (e.g., silica nanoparticles) contained in the nanocomposite have a lower refractive index than the polymer or polymer blend of the nanocomposite. Thus, in some embodiments, the nanoparticles lower the effective refractive index of the nanocomposite layer. Alternatively, or in addition, when the film is stretched to orient the high refractive index layer, the nanoparticles can inhibit orientation of the layer that increases the refractive index and would otherwise occur.

[0048] 5 is a schematic cross-sectional view of a multilayer film 500 of the present disclosure, illustrating substantially normally incident light 170 (e.g., within 20 degrees, 10 degrees, or 5 degrees of normally incident light). A portion of the light 170 is reflected as light 174, and a portion of the light 170 is transmitted as light 172.

[0049] In some embodiments, the multilayer film has an average light transmittance of at least 70 percent for unpolarized light at substantially normal incidence over a wavelength range extending from at least 450 nm to 650 nm. In some such embodiments, or in other embodiments, the multilayer film has an average light transmittance of no more than 50 percent for unpolarized light at substantially normal incidence over a wavelength range extending from at least 900 nm to 1000 nm. In some embodiments, the average light transmittance for unpolarized light at substantially normal incidence over a wavelength range extending from at least 450 nm to 650 nm is at least 70 percent, and the average light transmittance for unpolarized light at substantially normal incidence over a wavelength range extending from at least 900 nm to 1000 nm is no more than 30 percent.

[0050] FIG. 6 is a schematic plot of transmittance versus wavelength for a multilayer film according to some embodiments. The illustrated transmittances may be for light at substantially normal incidence. The multilayer film has an average transmittance of T1 over the wavelength range of λ1 to λ2 and an average transmittance of T2 over the wavelength range of λ3 to 4λ, where λ1<λ2<λ3<λ4. In some embodiments, when λ1-450 nm and λ2≧650 nm, T1 is at least 60 percent, or at least 70 percent, or at least 80 percent, or at least 90 percent. In some such embodiments, or in other embodiments, T2 is 50 percent or less, or 40 percent or less, or 30 percent or less, or 20 percent or less, or 10 percent or less when λ3-900 nm and λ4≧1000 nm.

[0051] In other embodiments, the multilayer film has a transmission that is substantially different from that shown schematically in Figure 6. For example, the multilayer film can have one or more reflection bands between λ1 and λ2 for one polarization state or for each of two orthogonal polarization states.

[0052] A suitable composition for use in the nanocomposite layer is a nanocomposite comprising at least one (meth)acrylic polymer (e.g., one (meth)acrylic polymer or two or more miscible (meth)acrylic polymers) and surface-modified metal oxide nanoparticles, where the surface-modified metal oxide nanoparticles are surface-modified with an acid-functional silane surface modifier, and the (meth)acrylic polymer is at least partially neutralized. The nanocomposite may be melt-processable into an optically transparent film. Melt-processable means that the nanocomposite is melt-processable, i.e., the nanocomposite can be heated and made to flow without causing decomposition. Melt-processable does not mean that the nanocomposite has been melt-processed, nor does it in any way indicate a processing step. The nanocomposite layer can also be made by a coating process from an aqueous dispersion onto a substrate such that the layer can be removed from the substrate.

[0053] FIG. 7 is a schematic cross-sectional view of a nanocomposite layer 310 including at least one polymer 108 (eg, a polymer matrix) and metal oxide nanoparticles 105 dispersed in the at least one polymer.

[0054] A wide variety of (meth)acrylic polymers are suitable for use in the nanocomposites of the present disclosure. The (meth)acrylic polymer comprises (meth)acrylic acid monomer units (i.e., acrylic acid monomer units, methacrylic acid monomer units, or both acrylic acid and methacrylic acid monomer units). In some embodiments, the (meth)acrylic polymer is a homopolymer of acrylic acid or methacrylic acid. In other embodiments, the (meth)acrylic polymer is a copolymer of at least one (meth)acrylic monomer unit that is acid-functional and at least one (meth)acrylate monomer that is not acid-functional. Additionally, the (meth)acrylic polymer can contain other non-(meth)acrylate monomers copolymerizable with the (meth)acrylic and (meth)acrylate monomers. Copolymers can be formed by polymerization or copolymerization using free-radical polymerization techniques. In some embodiments, at least one (meth)acrylic polymer comprises a copolymer containing (meth)acrylic acid and at least one comonomer. A wide variety of comonomers are suitable. Suitable comonomers include ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.

[0055] In some embodiments, the nanocomposite comprises at least one polymer and metal oxide nanoparticles dispersed in the at least one polymer of the nanocomposite. Each polymer can have a number average molecular weight of at least 10,000 grams / mole. The at least one polymer of the nanocomposite comprises a first polymer comprising (meth)acrylic acid monomer units (monomer units selected from the group consisting of methacrylic acid monomer units and acrylic acid monomer units). The metal oxide nanoparticles are surface-modified with a surface modifier comprising a carboxylic acid silane of Formula 1, as described elsewhere herein.

[0056] In some embodiments, the first polymer has a number average molecular weight of at least 12,000 g / mole or at least 15,000 g / mole. In some embodiments, each polymer of the at least one polymer has a number average molecular weight of at least 12,000 g / mole or at least 15,000 g / mole. For example, the at least one polymer can be a blend of a first and a second polymer, and each of the first and second polymers can have a number average molecular weight of at least 12,000 g / mole or at least 15,000 g / mole. The number average molecular mass of a polymer can be determined by gel permeation chromatography (GPC). Polymer characterization by GPC systems is well known. An example of such a system is the Viscotek TDAmax (Malvern Panalytical, part of Spectris). This system is equipped with multiple detectors for determining molecular weight. Absolute molecular weights of small polymers can be measured using right-angle light scattering detectors, and a direct output of the absolute molecular weight of a polymer without extrapolation can be obtained using low-angle light scattering. Additional detectors can be used to obtain information about polymer structure, for example, an intrinsic viscosity detector can be used to assess branching, and information related to copolymer composition can be investigated using a photodiode array UV detector if a UV-absorbing component is present. Further details of this equipment can be found from the supplier. In some embodiments, the first polymer, or each polymer of the at least one polymer, has a number average molecular weight of less than 100,000 grams / mole.

[0057] In some embodiments, the first polymer further comprises at least one monomer unit (e.g., a second type of monomer unit when a (meth)acrylic acid monomer unit is the first type of monomer unit) selected from the group consisting of ethylene, propylene, alkyl (meth)acrylate, aryl (meth)acrylate, alkaryl (meth)acrylate, acrylonitrile, and carbon monoxide. In some embodiments, the first polymer comprises at least one monomer unit (e.g., a second type of monomer unit) selected from the group consisting of ethylene and propylene. In some such embodiments, the first polymer further comprises at least one monomer unit (e.g., a third type of monomer unit) selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate. The first polymer can be, for example, a terpolymer. In some embodiments, the first polymer comprises (meth)acrylic acid monomer units, ethylene monomer units, propylene monomer units, or a combination of ethylene and propylene monomer units, and at least one alkyl (meth)acrylate monomer unit.

[0058] The at least one polymer can be a blend of two or more (meth)acrylic polymers. A wide variety of blends of (meth)acrylic polymers are suitable. Examples of suitable blends include blends of acrylic acid or methacrylic acid homopolymers and copolymers of acrylic acid or methacrylic acid and at least one additional monomer (e.g., selected from the group consisting of ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide). Other examples include blends of acrylic acid or methacrylic acid homopolymers and copolymers of acrylic acid or methacrylic acid and at least two additional monomers (e.g., the copolymers can be terpolymers). In some embodiments, the blends include copolymers of acrylic acid or methacrylic acid and at least one additional monomer and different copolymers of acrylic acid or methacrylic acid and at least one additional monomer. Yet other embodiments include blends of copolymers of acrylic acid or methacrylic acid and at least one additional monomer with copolymers of acrylic acid or methacrylic acid and at least two additional monomers. In addition, the blends may also include different copolymers of acrylic acid or methacrylic acid and at least two additional monomers.

[0059] In some embodiments, at least one polymer comprises a second polymer that is different from the first polymer. The first and second polymers may differ, for example, by having different molecular weights, different acid contents, different percent neutralization, different amounts of the same monomer units, and / or being compositionally distinct. In some embodiments, the second polymer is compositionally distinct from the first polymer. In this context, compositionally distinct may be understood to mean that at least one of the first and second polymers has at least one type of monomer unit that is not present in the other of the first and second polymers. For example, the first polymer may comprise two different monomer units (e.g., (meth)acrylic acid and either ethylene or propylene), and the second polymer may comprise the two monomer units of the first polymer plus a different third monomer unit (e.g., n-butyl acrylate or isobutyl acrylate). Compositionally distinct can include, for example, different acid types (e.g., methacrylic acid monomer units versus acrylic acid monomer units) and different ion types (ions that at least partially neutralize the ionomer can be considered part of the ionomer.) The second polymer can have a number average molecular weight of at least 10,000 grams / mole, or at least 12,000 grams / mole, or at least 15,000 grams / mole.

[0060] In some embodiments, the second polymer comprises (meth)acrylic acid monomer units. In some embodiments, the second polymer comprises at least one monomer unit selected from the group consisting of ethylene, propylene, alkyl (meth)acrylate, aryl (meth)acrylate, alkaryl (meth)acrylate, acrylonitrile, and carbon monoxide. In some embodiments, the second polymer comprises at least one monomer unit selected from the group consisting of ethylene and propylene. In some embodiments, the second polymer further comprises at least one monomer unit selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate. In some embodiments, the second polymer comprises (meth)acrylic acid monomer units, ethylene monomer units, propylene monomer units, or a combination of ethylene and propylene monomer units, and at least one alkyl (meth)acrylate monomer unit.

[0061] In some embodiments, the content of (meth)acrylic acid monomer units in the first polymer and, optionally, in the second polymer is greater than 12 weight percent. This has been found to aid in dispersing the first polymer and, optionally, the second polymer in water. In some embodiments, the content of (meth)acrylic acid monomer units in the first and second polymers is similar. This has been found, for example, to aid in polymer compatibility and improve optical properties. In some embodiments, the first polymer comprises (meth)acrylic acid monomer units at a first weight percent w1, and the second polymer comprises (meth)acrylic monomer units at a second weight percent w2. In some embodiments, at least one of w1 and w2 (w1, or w2, or each of w1 and w2) is greater than 12 weight percent, or greater than 13 weight percent, or greater than 14 weight percent, or greater than 15 weight percent. In some embodiments, at least one of w1 and w2 is less than 50 weight percent, or less than 30 weight percent, or less than 25 weight percent. In some such embodiments, or in other embodiments, |w1-w2| is less than 15 weight percent, or less than 14 weight percent, or less than 12 weight percent, or less than 10 weight percent, or less than 8 weight percent, or less than 7 weight percent, or less than 6 weight percent. Smaller values ​​of the difference |w1-w2| are preferred when both the first and second polymers are formed from aqueous dispersions, while in some embodiments, larger values ​​of the difference can be useful when the second polymer is added in a melt-processing step.

[0062] In some embodiments, the nanocomposite is formed from an aqueous dispersion comprising a first and a second polymer, as further described elsewhere herein. In some such embodiments, or in other embodiments, w1 and w2 each are greater than 12 weight percent, or greater than 13 weight percent, or greater than 14 weight percent, or greater than 15 weight percent. In some such embodiments, or in other embodiments, |w1-w2| is less than 10 weight percent, or less than 9 weight percent, or less than 8 weight percent, or less than 7 weight percent, or less than 6 weight percent. In some embodiments, |w1-w2| is in the range of 0 to 10 weight percent, or in the range of 0 to about 9 weight percent (e.g., 8.8, 9, or 9.2 weight percent can be considered to be about 9 weight percent). In some cases, when each of the two polymers in the dispersion contains two monomer units (e.g., a (meth)acrylic acid monomer unit and a second monomer unit such as ethylene or propylene), the acid content of the first polymer (w1) or the acid content of the second polymer (w2) can be, for example, in a range of greater than 27 weight percent. When one of the two polymers (e.g., the first polymer) has an acid content greater than 27%, the difference |w1-w2| can be, for example, up to 15 weight percent.

[0063] In some embodiments, a first nanocomposite or a first concentrated aqueous dispersion comprising a first polymer is melt processed with a second polymer (also referred to as an additional polymer) to form a nanocomposite (e.g., a second nanocomposite) comprising both the first and second polymers. In some such embodiments, the second polymer is not dispersible in water, with or without a neutralizing agent. In some embodiments, w2 can be less than 12 weight percent, and / or |w1 - w2| can be as high as 15 weight percent, for example. In some embodiments, w1 is greater than 12 weight percent, or greater than 13 weight percent, or greater than 14 weight percent, or greater than 15 weight percent, or in the range of 13 to 50 weight percent, or 13 to 35 weight percent, or 13 to 27 weight percent, or 14 to 22 weight percent, or 15 to 21.5 weight percent, or 15 to 21 weight percent, or 15 to 20.5 weight percent. In some such embodiments, or in other embodiments, w2 is at least 10 weight percent, or in the range of 10 weight percent to 25 weight percent, or to 21.5 weight percent, to 21 weight percent, or to 20.5 weight percent, or w2 can be in any of the ranges listed for w1. For example, in some embodiments, w1 is in the range of 15 to 20.5 weight percent and w2 is in the range of 10 to 20.5 weight percent, or in the range of 15 to 20.5 weight percent. In some embodiments, at least one of w1 and w2 is in the range of 14 to 22 weight percent, or in the range of 15 to 21.5 weight percent.

[0064] In some embodiments, the first polymer comprises (meth)acrylic acid monomer units at weight percent w1 and further comprises ethylene monomer units, and the second polymer comprises (meth)acrylic acid monomer units at weight percent w1 and further comprises ethylene monomer units. In some such embodiments, w1 is greater than 15 weight percent and |w1-w2| is less than 10 weight percent.

[0065] In some embodiments, the first polymer comprises (meth)acrylic acid monomer units at weight percent w1 and further comprises ethylene monomer units, and the second polymer comprises (meth)acrylic acid monomer units at weight percent w1, further comprises ethylene monomer units, and further comprises at least one monomer unit selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate. In some such embodiments, w1 is greater than 15 weight percent and |w1-w2| is less than 15 weight percent, or less than 13 weight percent, or less than 12 weight percent.

[0066] In some embodiments, the first polymer is at least partially neutralized. This means that the first polymer contains carboxylic acid groups and the protons of the carboxylic acid groups are replaced by cations, such as metal cations. Monovalent, divalent, and higher valence cations are suitable. In some embodiments, the first polymer is at least partially neutralized with a metal cation, an alkylammonium cation, or a combination thereof. In some embodiments, the first polymer is at least partially neutralized with a sodium cation, a calcium cation, a potassium cation, a zinc cation, a lithium cation, a magnesium cation, an aluminum cation, or a combination thereof. In some embodiments, the first polymer is at least partially neutralized with a non-metal cation. For example, the first polymer can be at least partially neutralized with an alkylammonium cation. In some embodiments, the nanocomposite is formed from the aqueous dispersion, as further described elsewhere herein. In some embodiments, in the aqueous dispersion, the first polymer is at least partially neutralized with at least one non-volatile neutralizing agent, or at least one volatile neutralizing agent, or a combination of volatile and non-volatile neutralizing agents. For example, in some embodiments, in the aqueous dispersion, the first polymer is at least partially neutralized with non-volatile amine cations, volatile amine cations (e.g., cations of dimethylethanolamine or ammonium cations), or a combination of volatile and non-volatile amine cations. The first polymer can be at least partially neutralized with a combination of different types of cations (e.g., metal and non-metal cations, or any combination of cations described herein). The first polymer can be an ionomer that is at least partially neutralized before being dispersed in the aqueous dispersion. In some embodiments, the ionomer is sufficiently neutralized so that no additional neutralizing agent needs to be added to the aqueous dispersion. In other embodiments, the ionomer is further at least partially neutralized with additional neutralizing agent added to the aqueous dispersion, as further described elsewhere herein.

[0067] In some embodiments, the second polymer is at least partially neutralized. In some embodiments, each polymer of the at least one polymer, or each polymer containing (meth)acrylic acid monomer units, is at least partially neutralized. The second polymer, or the other polymer of the at least one polymer, can be at least partially neutralized with any cation or combination of cations described for the first polymer.

[0068] Suitable ethylene (meth)acrylic acid copolymers can be obtained from commercial suppliers such as, for example, PRIMACOR 5980i from Dow Chemical Company (Midland, MI), NUCREL 925 and 960 from E.I. du Pont de Nemours and Company (Wilmington, DE), ESCOR 5200 from Exxon-Mobil (Irving, TX), and AC-5180 from Honeywell (Morris Plains, NJ). Suitable partially neutralized ethylene (meth)acrylic acid copolymers can be obtained from commercial suppliers such as, for example, SURLYN 1601, 1706, 1707, 7940, 9020, 9120, 8150 and PC-350 from E.I. du Pont de Nemours and Company (Wilmington, DE), and HPF 1000, for example.

[0069] A wide range of metal oxide nanoparticles are suitable. Examples of suitable metal oxide nanoparticles include metal oxides of silicon (silicon is considered a metalloid and is thus included in the list of metal oxides), titanium, aluminum, hafnium, zinc, tin, cerium, yttrium, indium, antimony, or mixed metal oxides thereof. Particularly more desirable metal oxide nanoparticles are those of silicon. For example, the metal oxide nanoparticles can be silica (SiO2) nanoparticles or SiOx (0 < x < 2) nanoparticles.

[0070] The size of such particles can be selected to avoid significant visible light scattering and have an average diameter of less than or equal to half the thickness of the layer in which they are incorporated. The surface-modified metal oxide nanoparticles can be particles having a primary or associated particle size greater than 1 nm (nanometer) and less than 200 nm (e.g., non-associated). In some embodiments, the particle size is greater than 4 nm, greater than 5 nm, greater than 10 nm, or greater than 20 nm. In some embodiments, the particle size is less than 190 nm, less than 150 nm, less than 100 nm, less than 75 nm, or less than 50 nm. Typically, the nanoparticles have sizes in the ranges of 4 to 190 nm, 4 to 100 nm, 4 to 75 nm, 10 to 50 nm, or 20 to 50 nm. In embodiments in which low optical haze is desired, particle sizes less than 100 nm, less than 75 nm, or less than 50 nm are typically preferred. In embodiments in which the low refractive index layer of a multilayer optical film comprises a nanocomposite layer herein, the average nanoparticle size can preferably be in the range of 4 to 20 nm. It is typically desirable for the nanoparticles to be non-associated. Particle size can be measured by a variety of methods, such as by transmission electron microscopy (TEM). Typically, commercially available metal oxide nanoparticles are supplied in a recited particle size or particle size range.

[0071] The nanoparticles are surface modified to improve compatibility with the polymer matrix material and to maintain the nanoparticles non-associated, non-weakly agglomerated, non-strongly agglomerated, or a combination thereof. The surface modification used to produce the surface-modified nanoparticles includes at least one acid-functional silane surface modifier. The acid-functional silane surface modifier has the general formula 1: [ka] [Wherein R1 is C1 to C 10 an alkoxy group, and R2 and R3 are independently C1 to C 10 Alkyl groups and C1-C 10 The group A may have a C1-C alkoxy group. 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16Heteroalkylene or heteroarylene groups, and C2-C 16 The linker group is selected from the group consisting of amide-containing groups, such as -(CH2) a -NH-(CO)-(CH2) b -type groups, where a and b are integers greater than or equal to 1, and (CO) is a carbonyl group, C=O. In some embodiments, A is an alkylene group having 1 to 3 carbon atoms.

[0072] While acid-functional silanes may be commercially available, one aspect of the present disclosure involves the synthesis of carboxylic acid-functional silanes of Formula 1. In addition to the synthetic process shown below, anhydride-functional silanes such as (3-triethoxysilyl)propylsuccinic anhydride, which can be obtained from commercial sources such as Gelest, Inc. (Morrisville, PA), can be used to prepare acid-functional silane surface modifiers.

[0073] In some embodiments, a solution is prepared from an organic acid anhydride dissolved in a first organic solvent. A second solution is prepared from an aminosilane in a second organic solvent. The two solutions are combined. The combined solution is continuously stirred at a suitable temperature and for a suitable duration to synthesize a carboxylic acid functional silane of Formula 1. In other embodiments, a solution is prepared from an organic acid anhydride dissolved in an organic solvent. The aminosilane is dissolved in the organic acid anhydride solution. The solution containing the organic acid anhydride and the aminosilane is continuously stirred at a suitable temperature and for a suitable duration to synthesize a carboxylic acid silane of Formula 1. The first and second organic solvents can be the same or different. When the first and second organic solvents are different, the first and second organic solvents are miscible. Both the first and second organic solvents are miscible with water.

[0074] Suitable organic acid anhydrides include succinic anhydride (3,4-dihydrofuran-2,5-dione), tetrahydrofuran-2,5-dione, 3-alkyltetrahydrofuran-2,5-diones such as 3-methyltetrahydrofuran-2,5-dione and 3-ethyltetrahydrofuran-2,5-dione, tetrahydropyran-2,6-dione, 3-alkyltetrahydropyran-2,6-diones such as 3-methyltetrahydropyran-2,6-dione and 3-ethyltetrahydropyran-2,6-dione, 4-alkyltetrahydropyran-2,6-diones such as 4-methyltetrahydropyran-2,6-dione, 4-ethyltetrahydropyran-2,6-dione, and 4,4'-methyltetrahydropyran-2,6-dione, and oxepane-2,7-dione. Suitable organic acid anhydrides are available from commercial sources such as Alfa Aesar (Ward Hill, Mass.) and Millipore Sigma (Burlington, Mass.). Succinic anhydride is a particularly suitable organic acid anhydride.

[0075] Suitable aminosilanes include aminopropyltrimethoxysilane, aminopropyltriethoxysilane, p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, N-phenylaminopropyltriethoxysilane, n-butylaminopropyltrimethoxysilane, n-butylaminopropyltriethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, and (N,N-diethyl-3-aminopropyl)triethoxysilane.Suitable aminosilanes can be obtained from commercial sources such as Gelest, Inc. (Morrisville, PA), Alfa Aesar (Ward Hill, MA), Millipore Sigma (Burlington, MA), and Momentive Performance Materials (Waterford, NY).A particularly suitable aminosilane is aminopropyltrimethoxysilane.

[0076] A wide variety of organic solvents can be used. Suitable organic solvents include N,N-dimethylformamide (DMF), which can be obtained from commercial sources such as OmniSolv (Billerica, MA).

[0077] In some embodiments, the surface-modified metal oxide nanoparticles are prepared by combining an aqueous nanodispersion of surface-unmodified metal oxide nanoparticles at a basic pH with a carboxylic acid-functional silane surface modifier, and reacting the carboxylic acid-functional silane surface modifier with the metal oxide nanoparticle surface, resulting in an aqueous nanodispersion of surface-modified metal oxide nanoparticles, the nanoparticles being surface-modified with a carboxylic acid. This may be done in a variety of ways. In some embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a solution of a carboxylic acid silane of Formula 1 in an organic solvent. In other embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a base and a solution of a carboxylic acid silane of Formula 1 in an organic solvent. In other embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a carboxylic acid silane of Formula 1. Generally, the carboxylic acid silane of Formula 1 is added at a concentration sufficient to modify 10-100% of the total metal oxide nanoparticle surface area in the nanodispersion. As noted above, the metal oxide nanoparticles can have a variety of sizes. Typically, the average particle size is greater than 1 nm and less than 200 nm. In some embodiments, the particle size is greater than 4 nm, greater than 5 nm, greater than 10 nm, or greater than 20 nm. In some embodiments, the particle size is less than 190 nm, less than 150 nm, less than 100 nm, less than 75 nm, or less than 50 nm. Typically, the nanoparticles have a size range of 4 to 190 nm, 4 to 100 nm, 4 to 75 nm, 10 to 50 nm, or 20 to 50 nm. For low haze, typical preferred ranges are 4 to 100 nm, 4 to 75 nm, or 4 to 50 nm. In some cases, because adding a solution of the carboxylic acid silane of Formula 1 tends to lower the pH, a base may be added to the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles to maintain the pH in the desired range. In some cases, the organic solvent is removed from the solution of the carboxylic acid silane in the organic solvent before combining the carboxylic acid silane with the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles.

[0078] Aqueous nanodispersions of unmodified metal oxide nanoparticles may be prepared, or in some embodiments, aqueous nanodispersions of unmodified metal oxide nanoparticles may be commercially available. Suitable surface-unmodified metal oxide nanoparticles include aqueous nanodispersions commercially available from Nalco Chemical Company (Naperville, IL) under the trade name "Nalco Colloidal Silicas," such as products NALCO 2326, 1130, DVSZN002, 1142, 2327, 1050, DVSZN004, 1060, and 2329K; from Nissan Chemical America Corporation (Houston, TX) under the trade name SNOWTEX, such as products ST-NXS, ST-XS, ST-S, ST-30, ST-40, ST-N40, ST-50, ST-XL, and ST-YL; and from Nyacol Nano Technologies, Inc. (Ashland, MA) under the trade name NEXSIL 5, 6, 12, 20, 85-40, 20A, 20K-30, and 20NH4. In some cases, the surface-unmodified metal oxide nanoparticles can be dispersed in an aqueous solution having a pH in the range of 8-12.

[0079] Suitable bases include ammonium hydroxide, which can be obtained from commercial sources such as Millipore Sigma (Burlington, MA).

[0080] Typically, the surface-modified metal oxide nanoparticles are used as a nanodispersion and the particles are not isolated. Another aspect of the present disclosure involves the preparation of a nanodispersion of surface-modified metal oxide nanoparticles without precipitation, gelation, weak aggregation, or strong aggregation, wherein the metal oxide nanoparticles have been surface-modified with a carboxylic acid silane of Formula 1.

[0081] In some embodiments, an aqueous nanodispersion of surface-unmodified metal oxide nanoparticles and a solution of a carboxylic acid silane of Formula 1 in an organic solvent are combined in a reactor and heated at a suitable temperature and duration to react the carboxylic acid silane of Formula 1 with the surface of the metal oxide nanoparticles. In other embodiments, an aqueous nanodispersion of surface-unmodified metal oxide nanoparticles, a base, and a solution of a carboxylic acid silane of Formula 1 in an organic solvent are combined in a reactor and heated at a suitable temperature and duration to react the carboxylic acid silane of Formula 1 with the surface of the metal oxide nanoparticles. In some embodiments, a solvent exchange is performed on the aqueous nanodispersion of surface-modified metal oxide nanoparticles and organic solvent to remove the organic solvent. In some embodiments, the reactor is open under reflux conditions; in other embodiments, the reactor is closed and under pressure. In some embodiments, the reactor is glass; in some embodiments, the reactor is stainless steel.

[0082] A wide range of loadings of surface-modified metal oxide nanoparticles in the nanocomposite is suitable. Typically, the nanocomposite contains at least 1 wt. % surface-modified metal oxide nanoparticles and up to 70 wt. % surface-modified metal oxide nanoparticles. In some embodiments, the surface-modified metal oxide nanoparticle concentration is 5 to 60 wt. % or 10 to 50 wt. Lower loadings of nanoparticles may be used when the nanocomposite layer is used as a low refractive index layer in a multilayer optical film. In some embodiments, the nanoparticles may be present in the nanocomposite layer in a range of, for example, 2% to 15 wt. %.

[0083] Additional additives may include, for example, flame retardants, heat stabilizers, anti-slip agents, neutralizing agents, ultraviolet absorbers, light stabilizers, antioxidants, crosslinking agents, mold release agents, catalysts, colorants, antistatic agents, defoamers, plasticizers, and other processing aids.

[0084] The aqueous dispersion can be used to form nanocomposites or ionomer layers that do not contain nanoparticles. It has been unexpectedly discovered that high molecular weight (meth)acrylic polymers (e.g., number-average molecular weight of at least 10,000 grams / mole) can be dispersed in water (e.g., with a suitable neutralizing agent), and the resulting aqueous dispersion is useful, for example, for creating nanocomposites with desired mechanical and optical properties. In some embodiments, the aqueous dispersion comprises water, at least one polymer dispersed in the water, and metal oxide nanoparticles dispersed in the water. The at least one polymer comprises a first polymer that includes (meth)acrylic acid monomer units and optionally has a number-average molecular weight of at least 10,000 grams / mole. The first polymer is at least partially neutralized. The metal oxide nanoparticles are surface-modified with a carboxylic acid silane surface modifier. The carboxylic acid silane surface modifier can be or include a carboxylic acid silane of Formula 1 described elsewhere herein. If a nanoparticle-free ionomer layer is desired, the metal oxide nanoparticles can optionally be omitted. [Example]

[0085] Exemplary Nanocomposites [Table 1]

[0086] NaOH Neutralizer Solution 3000 grams of deionized water was placed in a 3.78 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate (RCT Basic Model Magnetic Stirrer / Hot Plate Combination, IKA Works, Inc., Wilmington, NC) and stirring was initiated. 1156.1 grams of sodium hydroxide (NaOH) pellets were added to the jar. The NaOH pellets dissolved in the water, forming a clear solution.

[0087] KOH Neutralizer Solution 72 grams of deionized water was placed in a 0.24 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 28 grams of potassium hydroxide (KOH) chips were added to the jar. The KOH chips dissolved in the water, forming a clear solution.

[0088] LiOH Neutralizer Solution 90 grams of deionized water was placed in a 0.24 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 10 grams of lithium hydroxide (LiOH) granules were added to the jar. The LiOH granules dissolved in the water, forming a clear solution.

[0089] Zinc Neutralizer Solution 10 grams of zinc oxide (ZnO) was placed in a 3.78 liter clear glass jar. A Teflon-coated stir bar was added to the jar. 707 grams of deionized water was added to the jar. 394 grams of ammonium hydroxide solution (NH4OH) solution was added to the jar. The jar was placed on a stir plate and stirring was initiated. Stirring was continued overnight to obtain a clear solution.

[0090] Acid silane surface agent solution 225 grams of succinic anhydride (SA) was placed in a 4-liter amber glass jug. A Teflon-coated stir bar was added to the jug. The jug was placed on a stir plate. 2500 grams of N,N-dimethylformamide (DMF) was added to the jar and stirring was initiated. Once the succinic anhydride had dissolved, 400 grams of 3-aminopropyltrimethoxysilane (AMINO-TMOS) was added to the jug. The contents of the jug were allowed to stir at room temperature for 24 hours to complete the reaction and form the acid silane in the DMF.

[0091] Ionic Elastomer Dispersion Dispersion D1, D4~D10: Dispersions D1, D4, and D10 illustrate the preparation of ionic elastomer dispersions in an open (atmospheric) reactor. The masses of each component are listed in Table 2. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). Unneutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. Neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a clear glass jar. The process conditions, along with the pH of the resulting dispersions, are detailed in Table 3.

[0092] Dispersion D2: Dispersion D2 illustrates the preparation of an ionic elastomer dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 2. Deionized water was placed in a 37.85 liter stainless steel reactor. Unneutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 30 rpm. Neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. Agitation was increased to 60 rpm. The reactor was sealed to prevent material loss. Heating was initiated to a set-point temperature of 100°C. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C with continuous agitation for 2.5 hours. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. The process conditions, along with the pH of the resulting dispersions, are detailed in Table 3.

[0093] Dispersion D3: Dispersion D3 illustrates the preparation of an ionic elastomer dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 2. Deionized water was placed in a 265-liter stainless steel reactor. Unneutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated. A neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. The reactor was sealed to prevent material loss. Heating was initiated at a set-point temperature of 100°C. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 4.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a 208-liter plastic drum. The pH of the resulting dispersion, along with the process conditions, is detailed in Table 3.

[0094] Dispersion D11: Dispersion D11 illustrates the preparation of an ionic elastomer dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 2. Deionized water was placed in a 37.85-liter stainless steel reactor. Unneutralized (meth)acrylic copolymer elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 60 rpm. Neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. Agitation was increased to 120 rpm. The reactor was sealed to prevent material loss. Heating was initiated at a set-point temperature of 100°C. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93-liter plastic-lined metal pails. The process conditions, along with the pH of the resulting dispersions, are detailed in Table 3.

[0095] Dispersion D12: Dispersion D12 illustrates the preparation of an ionic elastomer dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 2. Deionized water was placed in a 37.85-liter stainless steel reactor. Unneutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. Neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. Heating was initiated at a set-point temperature of 150°C. The reactor was sealed to allow processing at higher temperatures and prevent material loss. After the batch temperature reached 150°C, the reactor contents were maintained at 150°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93-liter plastic-lined metal pails. The process conditions, along with the pH of the resulting dispersions, are detailed in Table 3. [Table 2] [Table 3]

[0096] Dispersions D13~D15, D17~D21, D23, D24: Dispersions D13-D15, D17-D21, D23, and D24 illustrate the preparation of ionic elastomer dispersions in an open (atmospheric) reactor. The masses of each component are listed in Table 6. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). Pre-neutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. Neutralizing agent was added to the reactor to achieve 75% neutralization of the (meth)acrylic elastomer. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersions were filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to clear glass jars. Characterization results, along with process conditions, are detailed in Table 7. The pH of each dispersion was measured. Particle size analysis showed that all dispersions were unimodal with dispersed phase sizes less than 100 nm. The dispersions exhibit varying degrees of haze, which correlates with dispersed phase size. Similar values ​​for dry weight of the unfiltered and filtered dispersions indicate that the elastomer is fully dispersed.

[0097] Dispersion D16: Dispersion D16 illustrates the preparation of an ionic elastomer dispersion in an open (atmospheric) reactor. The masses of each component are listed in Table 6. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). Pre-neutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. No neutralizing agent was added to the reactor. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours under continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a clear glass jar. The process conditions and characterization results are detailed in Table 7. The pH of the resulting dispersion was 9.5. Particle size analysis showed a unimodal dispersed phase size of 44.26 nm. The dispersion was turbid with a measured haze of 11.6%. Similar values ​​for the dry weight of the unfiltered and filtered dispersions indicate that the elastomer was completely dispersed.

[0098] Dispersion D22: Dispersion D22 illustrates the preparation of an ionic elastomer dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 6. Deionized water was placed in a 37.85 liter stainless steel reactor. Pre-neutralized (meth)acrylic elastomer in pellet form was added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was started at 30 rpm. The neutralizing agent was added to the reactor. Agitation was increased to 120 rpm. The reactor was sealed to allow for processing at higher temperatures and prevent material loss. Heating was initiated at a set-point temperature of 150°C. After the batch temperature reached 150°C, the reactor contents were maintained at 150°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. The characterization results, along with the process conditions, are detailed in Table 7. The pH of the resulting dispersion was 11.5. Particle size analysis showed a bimodal dispersion with sizes of 23.25 nm and 140.5 nm. The dispersion was milky white with a measured haze of 81.6%. Similar values ​​for the dry weight of the unfiltered and filtered dispersions indicate that the elastomer was fully dispersed. [Table 4] [Table 5]

[0099] Ionic elastomer blend dispersion Dispersion D25: Dispersion D25 illustrates the preparation of an ionic elastomer blend dispersion in an open (atmospheric) reactor. The masses of each component are listed in Table 10. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). Two unneutralized (meth)acrylic elastomers, both in pellet form, were added to the reactor to obtain a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. Two neutralizing agents were added to the reactor. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a clear glass jar. Characterization results, along with process conditions, are provided in Table 11. The pH of the resulting dispersion was 10.5. Particle size analysis showed a bimodal dispersion size of 47.09 and 5350 nm, with the smaller size accounting for 99.1% of the result. The dispersion was turbid with a measured haze of 22.6%. Similar values ​​for the dry weight of the unfiltered and filtered dispersions indicate that the two elastomers were completely dispersed.

[0100] Dispersion D26, D27: Dispersions D26 and D27 illustrate the preparation of ionic elastomer blend dispersions in a closed (pressurized) reactor. The masses of each component are listed in Table 10. Deionized water was charged to a 37.85 liter stainless steel reactor. One pre-neutralized (meth)acrylic acid elastomer and one unneutralized (meth)acrylic acid elastomer, both in pellet form, were added to the reactor to provide a 15 weight percent elastomer dispersion. Agitation was started at 30 rpm. The neutralizing agent was added to the reactor. Agitation was increased to 120 rpm. The reactor was sealed to allow processing at higher temperatures and prevent material loss. Heating was initiated at a set point temperature of 150°C. After the batch temperature reached 150°C, the reactor contents were maintained at 150°C for 2.5 hours under continuous agitation. The resulting dispersions were filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. The characterization results, along with the process conditions, are detailed in Table 11. The pH of the resulting dispersions was 10.5 and 11.0 for D26 and D27, respectively. Particle size analysis showed bimodal dispersions for both dispersions D26 and D27 with similar dispersed phase sizes. Both dispersions were milky white with measured hazes of 61.2% and 48.0% for D26 and D27, respectively. Similar values ​​for dry weight of the unfiltered and filtered dispersions indicate that the two elastomers were fully dispersed.

[0101] Dispersion D28: Dispersion D28 illustrates the preparation of an ionic elastomer blend dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 10. Deionized water was charged to a 37.85 liter stainless steel reactor. One pre-neutralized (meth)acrylic acid elastomer and one unneutralized (meth)acrylic acid elastomer, both in pellet form, were added to the reactor to provide a 15 weight percent elastomer dispersion. Agitation was started at 30 rpm. The neutralizing agent was added to the reactor. Agitation was increased to 120 rpm. The reactor was sealed to allow processing at higher temperatures and prevent material loss. Heating was initiated at a set point temperature of 150°C. After the batch temperature reached 150°C, the reactor contents were maintained at 150°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. Characterization results, along with process conditions, are detailed in Table 11. The pH of the resulting dispersion was 11.5. Particle size analysis showed a bimodal distribution of dispersed phase sizes of 12.26 and 194.0 nm. The dispersion was milky white with a measured haze of 88.1%. Similar values ​​for the dry weight of the unfiltered and filtered dispersions indicate complete dispersion of the two elastomers.

[0102] Dispersion D29: Dispersion D29 illustrates the preparation of an ionic elastomer blend dispersion in a closed (pressurized) reactor. The masses of each component are listed in Table 10. Deionized water was charged to a 37.85 liter stainless steel reactor. One pre-neutralized (meth)acrylic acid elastomer and one unneutralized (meth)acrylic acid elastomer, both in pellet form, were added to the reactor to provide a 15 weight percent elastomer dispersion. Agitation was started at 30 rpm. The neutralizing agent was added to the reactor. Agitation was increased to 120 rpm. The reactor was sealed to allow processing at higher temperatures and prevent material loss. Heating was initiated at a set point temperature of 140°C. After the batch temperature reached 140°C, the reactor contents were maintained at 140°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. Characterization results, along with process conditions, are detailed in Table 11. The pH of the resulting dispersion was 11.5. Particle size analysis showed a bimodal distribution of dispersed phase sizes of 26.21 and 290.0 nm. The dispersion was milky white with a measured haze of 70.2%. Similar values ​​for the dry weight of the unfiltered and filtered dispersions indicate complete dispersion of the two elastomers.

[0103] Dispersion D30~D33, D35, D36: Dispersions D30-D33, D35, and D36 illustrate the preparation of ionic elastomer blend dispersions in an open (atmospheric) reactor. The masses of each component are listed in Table 10. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). Two pre-neutralized (meth)acrylic elastomers, both in pellet form, were added to the reactor to yield a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. The neutralizing agent was added to the reactor. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a clear glass jar. Characterization results, along with process conditions, are provided in Table 11. The pH of the resulting dispersions ranged from 10.0 to 11.0. Particle size analysis showed that Dispersions D30, D31, D32, and D35 exhibited a unimodal dispersion size, while Dispersions D33 and D36 exhibited a bimodal dispersion. The dispersions exhibited varying degrees of turbidity, which correlated with the haze values ​​presented in Table 11. Haze was significantly lower for dispersions with a unimodal dispersed phase versus a bimodal one. Similar values ​​for dry weight of the unfiltered and filtered dispersions indicate that the two elastomers were fully dispersed.

[0104] Dispersion D34: Dispersion D34 illustrates the preparation of an ionic elastomer blend dispersion in an open (atmospheric) reactor. The masses of each component are listed in Table 10. Deionized water was placed in a 2-liter cylindrical, clear glass reactor (Ace Glass, Vineland, NJ). One pre-neutralized (meth)acrylic acid elastomer and one unneutralized (meth)acrylic acid elastomer, both in pellet form, were added to the reactor to yield a 15 weight percent elastomer dispersion. Agitation was initiated at 120 rpm. The neutralizing agent was added to the reactor. Heating was initiated at a set-point temperature of 100°C, and the reactor was operated under reflux. After the batch temperature reached 100°C, the reactor contents were maintained at 100°C for 2.5 hours with continuous agitation. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to a clear glass jar. The characterization results, along with the process conditions, are detailed in Table 11. The pH of the resulting dispersion was 10.0. Particle size analysis showed a monomodal dispersed phase size of 30.29 nm. The dispersion was turbid with a haze of 7.2%. Similar values ​​of dry weight for the unfiltered and filtered dispersions indicate that the two elastomers were completely dispersed. [Table 6] [Table 7] [Table 8]

[0105] Dispersion D37~D40: Dispersions D37-D40 illustrate the preparation of ionic elastomer blend dispersions by blending two (meth)acrylic elastomer dispersions. 100 grams of the two dispersions shown in Table 13 were mixed on a stir plate at room temperature for 20 minutes to form the ionic elastomer blend dispersions. Characterization results are shown in Tables 14 and 15. Table 14 shows that all four dispersions were milky white, consistent with one or both unblended dispersions. The pH of the resulting dispersions ranged from 10.5 to 11.0. Particle size analysis indicated the blend dispersions had either unimodal or bimodal dispersed phase sizes. The milky appearance of the blend dispersions correlates with high haze, ranging from 67.8 to 99.2%. Similar values ​​for dry weight of the unfiltered and filtered dispersions indicate that the two elastomers are fully dispersed. [Table 9] [Table 10] [Table 11]

[0106] Ionic Elastomer Coating Coatings C1 to C12: Coatings C1-C12 exemplify transparent ionic elastomer coating formulations. Each dispersion was coated onto an unprimed PET substrate film in a continuous roll-to-roll process in which the dispersion was metered onto a moving web through a slot die. The ionic elastomer dispersion was metered by a metering pump and mass flow meter. The volumetric flow rates for each coating formulation are shown in Table 16. Volatile components of the coating formulation (i.e., the ionic elastomer dispersion) were removed in a three-zone air flotation oven. The temperatures of each zone, from oven inlet to outlet, were 65.6°C, 79.4°C, and 135°C, respectively, and each oven section had a nominal length of 3.05 m. Table 17 shows the nominal coating thickness of 10 micrometers and the characterization results, including a visible transmittance of greater than 93% and a haze of less than 1%. Note that the optical characterization includes the PET substrate and coating. The 75 μm PET substrate for all coatings C1-C78 had a transmittance of 91.9%, a haze of 0.65%, and a clarity of 99.9%. [Table 12] [Table 13]

[0107] Coating C13~C22: Coatings C13-C22 further illustrate the formulation of transparent ionic elastomeric coatings. Coatings C13-C22 were coated in the same manner as coatings C1-C12. Table 17A shows the nominal coating thickness of 10 μm and the characterization results, including a visible transmittance of greater than 93% and a haze of less than 1%. Note that the optical characterization includes the PET substrate and coating. [Table 14] [Table 15]

[0108] Ionic Elastomer Blend Coating Coating C23~C30: Coatings C23-C30 illustrate the formulation of transparent ionic elastomer blend coatings. Coatings C23-C30 were coated in the same manner as coatings C1-C12. Table 21 shows the characterization results, including a nominal coating thickness of 10 μm and a visible transmittance of greater than 93% and a haze of less than 1%, except for coating C28. Note that the optical characterization includes the PET substrate and coating. [Table 16] [Table 17] [Table 18]

[0109] Nanoparticle dispersion Dispersion D41: Dispersion D41 demonstrates the preparation of a silica nanoparticle dispersion in which the nanoparticle surface was modified with carboxylic acid functional groups. The carboxylic acid functional groups were required to ensure compatibility between the nanoparticles and the (meth)acrylic elastomer. 400 grams of aqueous colloidal silica dispersion (NALCO 2327) was placed in a 0.95 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 317.5 grams of deionized water was added to the jar. 132.5 grams of acid silane surface agent solution was added to the jar. The contents of the jar were mixed for 20 minutes. The stir bar was removed from the jar, and the contents were placed in a preheated 80°C oven for 24 hours. After 24 hours, the jar was removed from the oven, and the nanoparticle dispersion was allowed to cool to room temperature under ambient conditions. The pH of the nanoparticle dispersion was 5.5, and the nanoparticle concentration was calculated to be 19.3 wt%.

[0110] Dispersion D42: Dispersion D42 demonstrates the preparation of a silica nanoparticle dispersion in which the nanoparticle surface is modified with carboxylic acid functional groups. The carboxylic acid functional groups are required to ensure compatibility between the nanoparticles and the (meth)acrylic elastomer. 49.33 kg of aqueous colloidal silica dispersion (NALCO 2327) was placed in a 2.67 liter stainless steel reactor. Agitation was initiated. 15.58 kilograms of acid silane surface agent solution was added to the reactor. The reactor contents were heated to 80°C. Upon reaching 80°C, the reactor was sealed, and the reactor contents were maintained at 80°C with continuous stirring for 24 hours. After 24 hours, the reactor contents were cooled, filtered through a 50 μm filter, and transferred to two 18.93 liter plastic-lined metal drums. The pH of the nanoparticle dispersion was 5.5, and the nanoparticle concentration was calculated to be 31.3 wt%. [Table 19]

[0111] Dispersion D43: To increase the pH of the silica nanoparticle dispersion in D42, ammonium hydroxide solution was added. 3,000 grams of nanoparticle dispersion D42 was placed in a 3.78 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 71.2 grams of a nominally 28% by weight aqueous ammonium hydroxide solution was added to the nanoparticle dispersion. The contents of the jar were mixed for 20 minutes, and then the stir bar was removed from the jar. The pH of the nanoparticle dispersion was calculated to be 10.0, and the nanoparticle concentration was calculated to be 30.6% by weight. [Table 20]

[0112] Ionic Elastomer Nanocomposite Coatings Coating C39~C48: Coatings C39-C48 illustrate the preparation of transparent ionic elastomer nanocomposite coatings. The mass of each dispersion used in each coating formulation is detailed in Table 24. For each coating, the mass of ionic elastomer dispersion was placed in a clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. The desired mass of nanoparticle dispersion was added to the ionic elastomer dispersion. The ionomer / nanoparticle dispersion was mixed for 20 minutes. Each ionomer / nanoparticle dispersion was coated onto unprimed PET substrate film in the same manner as coatings C1-C12. Table 25 shows the nominal coating thickness of 10 μm and the characterization results, including visible transmittance greater than 93% and haze less than 1%, except for coating C44, which contained 60 wt% nanoparticles. Coatings C39-C43 illustrate the minimal effect of nanoparticle concentration on coating optical components from 10 to 50 wt% nanoparticles. Coatings C39-C48 further illustrate the good optical performance for various ionic elastomers with nanoparticle loadings as high as 40 wt%. Note that the optical characterization includes the PET substrate and coating. [Table 21] [Table 22]

[0113] Coating C49~C59: Coatings C49-C59 further illustrate the preparation of transparent ionic elastomer nanocomposite coatings. Ionomer / nanoparticle coating formulations were prepared in the same manner as described for Coatings C39-C48. Each ionomer / nanoparticle dispersion was coated onto unprimed PET substrate film in the same manner as Coatings C1-C12. Formulation and coating details are provided in Table 26. Table 27 shows the characterization results, including a nominal coating thickness of 10 μm and visible transmittance greater than 92-93% and haze less than 1%. Coatings C49-C59 illustrate the minimal effect of nanoparticle concentration on coating optical components from 10-60 wt% nanoparticles. Coatings C39-C48 further illustrate the good optical performance for various ionic elastomers with a high nanoparticle loading of 40 wt%. Coating C58 was intentionally coated with a volatile neutralizing agent that was removed during the coating process by evaporation. Note that the optical characterization includes the PET substrate and coating. [Table 23] [Table 24]

[0114] Ionic elastomer nanocomposite blend coatings Coating C60~C68: Coatings C60-C68 illustrate the preparation of transparent ionic elastomer nanocomposite blend coatings. Formulation and coating details are provided in Table 29. The preparation of ionomer blend dispersions for coatings C63-C66 is described in Dispersions D52-D54 and Table 29. For each coating, the mass of ionic elastomer blend dispersion was placed in a clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. The desired mass of nanoparticle dispersion was added to the ionic elastomer blend dispersion. The ionomer / nanoparticle dispersion was mixed for 20 minutes. Each ionomer blend / nanoparticle dispersion was coated onto unprimed PET substrate film in the same manner as coatings C1-C12. Table 32 shows the nominal coating thickness of 10 μm and the characterization results, including visible transmittance greater than 92-93% and haze less than 1%, for nanocomposite coatings with up to 40 wt% nanoparticles. Note that the optical characterization includes the PET substrate and coating. [Table 25]

[0115] Dispersion liquid D52~D54: Dispersions D52-D54 illustrate the preparation of ionic elastomer blend dispersions for use in ionic elastomer nanocomposite coatings C60-C62. 300 grams of Dispersion D22 was placed in a 0.95 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 300 grams of Ionic Elastomer Dispersion D24 was added to Dispersion D22 to form Ionic Elastomer Blend Dispersion D52. After combining Dispersions D22 and D24, Dispersion D52 was mixed for 20 minutes. Similarly, Ionic Elastomer Blend D53 was formed by mixing Dispersions D22 and D27, and Dispersion D54 was formed by combining Dispersions D24 and D19, as detailed in Table 30. [Table 26]

[0116] Coating C69~C78: Coatings C69-C78 further illustrate the preparation of ionic elastomer nanocomposite blend coatings. Formulation and coating details are provided in Table 31. Each ionomer blend / nanocomposite dispersion was prepared in the same manner as coatings C60-C68. Each ionomer blend / nanoparticle dispersion was coated onto unprimed PET substrate films in the same manner as coatings C1-C12. Table 32 shows the characterization results for coatings C69-C78, including a nominal coating thickness of 10 μm and visible transmittance greater than 92-93% and haze less than 1%, for nanocomposite coatings with up to 40 wt% nanoparticles. Note that the optical characterization includes the PET substrate and coating. [Table 27] [Table 28]

[0117] Ionic elastomer nanocomposite films Film F1~F10: Films F1-F10 exemplify ionic elastomer nanocomposite films prepared by melt processing. Composition details for Films F1-F11 are provided in Table 33. The aforementioned nanocomposite coating was separated from the PET substrate and used as the ionic elastomer nanocomposite during melt processing. For Films F1-F3 and F7-F10, pure (meth)acrylic elastomer was melt processed along with the nanocomposite coating to reduce the nanoparticle concentration. For Films F4-F6, only the nanocomposite was melt processed. For Film F8, a neutralizing agent was added during the melt process. The ionic elastomer nanocomposites were melt processed using a Plasti-corder (CW Brabender Instruments, Inc., South Hackensack, NJ). All nanocomposite formulations were compounded at 150 °C and 75 rpm for 15 minutes. After compounding, the nanocomposites were pressed into films using an Auto Series hot press (Carver Inc., Wabash, IN). In the hot-pressing process, a portion of the compounded material was placed between polyimide sheets and then between polished aluminum plates. A two-stage hot-pressing process was used to press the nanocomposites into films. First, the nanocomposites were pressed at 900 kgf for 5 minutes at the selected press temperature. Most nanocomposites were pressed at 125°C. Higher press temperatures were required for nanocomposites with higher nanoparticle loadings. The hot-pressing temperatures are detailed in the attached table. In the second stage, the press automatically increased the pressure to 10,900 kgf for 0.1 minutes at the same temperature, after which the press automatically opened. The pressed films were removed from between the aluminum sheets and allowed to cool to room temperature before removing the polyimide sheets. Characterization of the pressed films, including thickness and optical properties, is detailed in Table 34. Except for the nanocomposite film with 60 wt% nanoparticles, the nanocomposite films exhibit visible transmittance greater than 90%. With the exception of films F6 and F9, the remaining eight nanocomposite films exhibit hazes ranging from 2.7 to 4.0%. Thermogravimetric analysis (TGA) was performed on films F1 to F4 to determine the nanoparticle concentration.The solids content of films F1-F4 correlates well with the expected nanoparticle concentration, as shown in Table 34. The presence of metal ions in the nanocomposites is expected to increase the percent solids as determined by TGA. [Table 29] [Table 30]

[0118] Film F12~F21: Films F12-F21 further exemplify ionic elastomer nanocomposite films produced by melt processing. Films F12-F21 were processed in a similar manner to Films F1-F11; i.e., the ionic elastomer nanocomposite of the coated film was removed from the PET substrate and melt processed. Compositional details for Films F12-F21, along with the temperature at which the nanocomposite was pressed into a film, are provided in Table 35. Films F12-F21 further exemplify melt-processed ionic elastomer nanocomposite films with nanoparticle loadings of 10-40 wt%. Film F17 exemplifies an ionic elastomer nanocomposite film in which the neutralizing agent was intentionally removed during processing. Film F16 exemplifies an ionic elastomer nanocomposite film with neutralization during melt processing. Film F17 exemplifies the use of different neutralizing agents in the dispersion and in the melt-processed film. [Table 31] [Table 32]

[0119] Ionic elastomer nanocomposite blend films Film F22~F43: Films F22-F43 illustrate the preparation of ionic elastomer nanocomposite blend films by melt processing. Films F22-F43 were processed in a similar manner to Films F1-F11; that is, the ionic elastomer nanocomposite coating was separated from the PET substrate film and melt processed. For Films F22-F43, the nanocomposite coating was melt processed with a second (meth)acrylic elastomer different from that of the coating to form the ionic elastomer nanocomposite blend films. Composition details and hot-press temperatures are provided in Tables 37 and 38. Characterization results in Table 39 show visible transmittances of over 91% and haze values ​​ranging from 2.9 to 26.6%. High haze values ​​of 10.1 to 26.6% correlate with higher acidity differences between the (meth)acrylic elastomers in the blends. Optical characterization indicated that transparent ionic elastomer nanocomposites can be achieved with higher acidity differences by melt processing than are accessible by dispersion and coating alone. The TGA results for films F38-F41 correlate well with the calculated nanoparticle loadings. The TGA results provide technical support not only for the melt-processed nanocomposite blend films, but also for the coated nanocomposite films from which they are derived. [Table 33] [Table 34] [Table 35]

[0120] Film F44~F48: Films F44-F48 further exemplify melt-processed ionic elastomer nanocomposite blend films. Films F44-F48 were processed in a similar manner to Films F22-F43. That is, the ionic elastomer nanocomposite coating was separated from the PET substrate film and melt-processed with a second (meth)acrylic elastomer to form the ionic elastomer nanocomposite blend. For Films F44-F48, the second ionic elastomer is a neutralized terpolymer that is not dispersible in water but was found to be easily melt-processable. Composition details, along with hot-press temperatures, are provided in Table 40. Characterization results in Table 41 indicate that the ionic elastomer nanocomposite blend films exhibit visible transmittance greater than 93% and haze less than 4%. [Table 36] [Table 37]

[0121] Test Method pH: The pH of the ionomer aqueous dispersion was measured using pH test paper (Ricca Chemical Co., Arlington, TX).

[0122] Percent solids by weight: The weight percent solids were measured for both the filtered and unfiltered dispersions. For the unfiltered dispersions, a nominal 3-gram sample of the dispersion was placed in a small Pyrex Petri Dish (Corning Inc., Corning, NY). The sample was placed in a preheated oven at 120°C for 12 hours, after which the sample was removed from the oven and allowed to cool. The masses of the dried dispersion and dish were measured. The weight percent solids was calculated from the mass of the dish, the mass of the dish plus the dispersion, and the mass of the dish plus the dried dispersion according to the following formula: For the filtered dispersions, a nominal 3-gram sample of the dispersion was filtered into a small Pyrex Petri Dish through a 1-micron glass fiber filter (Pall Corp., Port Washington, NY) connected to a disposable syringe (Becton, Dickinson and Co., Franklin Lakes, NJ). The sample was placed in a preheated oven at 120°C for 12 hours, after which the sample was removed from the oven and allowed to cool. The mass of the dried dispersion and dish was measured. The weight percent solids was calculated from the mass of the dish, the mass of the dish + dispersion, and the mass of the dish + dried dispersion according to the following formula: All weight percent solids measurements were performed in duplicate.

number

[0123] Particle size: Particle size was measured using a Zetasizer NS (Malvern Instruments Ltd., Worcestershire, UK). Dispersions were diluted 1:10, 1:100, 1:1,000, and sometimes 1:10,000 with NaOH solution that matched the pH of the dispersion. Three measurements were taken at each dilution and averaged. Particle size was selected once there was no significant change with dilution.

[0124] Transmittance, Haze, and Clarity (THC) Luminous transmission, haze, and clarity were measured according to ASTM D1003-00 using a Model 4725 Gardner Haze-Guard Plus (BYK-Gardner, Columbia, MD).

[0125] Hayes: The haze of the liquid dispersions was measured with an Ultrascan PRO spectrophotometer (HunterLab, Reston, VA).

[0126] Film Thickness: Film thickness was measured using a digital indicator model H0530E (Mitutoyo America Corporation, Aurora, IL).

[0127] Coating Thickness: The coating thickness was measured using white light interferometry and FTM-ProVis Lite software.

[0128] Thermogravimetric analysis (TGA): The nanoparticle concentration in melt-processed nanocomposite films was measured by TGA. A model TGA Q500 (TA Instruments, New Castle, DE) was used. Approximately 5 milligrams of nanocomposite film or nanocomposite blend film sample was placed on a pre-tared platinum pan in the instrument. The nanoparticle concentration was determined as the final weight of the sample after heating from 35°C to 700°C at 20°C / min.

[0129] Nuclear magnetic resonance (NMR): The synthesized carboxylic acid silane chemistry was confirmed using a Bruker Avance 600 MHz NMR spectrometer equipped with a cryogenically cooled probehead (Bruker Corporation, Billerica, MA). The carboxylic acid silane / DMF solution was mixed with deuterated DMF. One-dimensional (1D) 1 H and 13C NMR data were collected at 25° C. One of the residual proton-solvent resonances was used as a secondary chemical shift reference in the proton dimension (δ=8.03 ppm). [Example]

[0130] Preparation example 1: NaOH solution 3000 grams of deionized water was placed in a 3.78 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate (RCT Basic Model Magnetic Stirrer / Hot Plate Combination, IKA Works, Inc., Wilmington, NC) and stirring was initiated. 1156 grams of sodium hydroxide (NaOH) pellets were added to the jar. The NaOH pellets dissolved in the water, forming a clear solution.

[0131] Preparation Example 2: Acid silane solution 225 grams of succinic anhydride (SA) was placed in a 4-liter amber glass jug. A Teflon-coated stir bar was added to the jug. The jug was placed on a stir plate. 2500 grams of N,N-dimethylformamide (DMF) was added to the jar and stirring was initiated. Once the succinic anhydride had dissolved, 400 grams of 3-aminopropyltrimethoxysilane (AMINO-TMOS) was added to the jug. The contents of the jug were allowed to stir at room temperature for 24 hours to complete the reaction and form the acid silane in the DMF.

[0132] Preparation Example 3: Ionic elastomer dispersion 27.76 kilograms of deionized water was placed in a 37.85 liter stainless steel reactor. 5.11 kilograms of SURLYN 9120 in pellet form was added to the reactor to provide a 15 weight percent elastomer dispersion. SURLYN 9120 was a Zn ++The (meth)acrylic acid elastomer was pre-neutralized with 38% neutralization by NaOH. Agitation was started at 30 rpm. 1.20 kilograms of NaOH solution (Preparation Example 1) was added to the reactor. Agitation was increased to 120 rpm. The reactor was sealed to allow for higher temperature processing and prevent material loss. Heating was initiated at a set-point temperature of 150°C. After the batch temperature reached 150°C, the reactor contents were maintained at 150°C for 2.5 hours with continuous stirring. The resulting dispersion was filtered through a 200 μm sock filter (Pall Corp., Port Washington, NY) and transferred to two 18.93 liter plastic-lined metal pails. Characterization results, along with process conditions, are detailed in Table 2. The pH of the resulting dispersion was 11.5. Particle size analysis showed a bimodal dispersion with sizes of 23.25 nm and 140.5 nm. The dispersion was milky white with a measured haze of 81.6%. Similar values ​​for dry weight of the unfiltered and filtered dispersions indicate that the elastomer was completely dispersed. [Table 38]

[0133] Preparation example 4: Silica nanoparticle dispersion 49.33 kg of aqueous colloidal silica dispersion (NALCO 2327) was placed in a 75.71 liter stainless steel reactor. Agitation was initiated. 15.58 kilograms of acid silane solution (Preparation Example 2) was added to the reactor. The reactor contents were heated to 80°C. Upon reaching 80°C, the reactor was sealed and the reactor contents were maintained at 80°C with continuous stirring for 24 hours. After 24 hours, the reactor contents were cooled, filtered through a 50 μm filter, and transferred to two 18.93 liter plastic-lined metal drums. The pH of the nanoparticle dispersion was 5.5, and the nanoparticle concentration was calculated to be 31.3 wt%.

[0134] Preparation example 5: Silica nanoparticle dispersion 3000 grams of silica nanodispersion (Preparation Example 4) was placed in a 3.78 liter clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 71.2 grams of a nominally 28% by weight ammonium hydroxide solution was added to the nanoparticle dispersion. The contents of the jar were mixed for 20 minutes, and then the stir bar was removed from the jar. The pH of the nanoparticle dispersion was 10.0, and the nanoparticle concentration was calculated to be 30.6% by weight.

[0135] Preparation Example 6: Ionic Elastomer Nanocomposite Coating 1319 grams of the ionic elastomer dispersion (Preparation Example 3) was placed in a clear glass jar. A Teflon-coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was initiated. 431 grams of the silica nanoparticle dispersion (Preparation Example 5) was added to the jar. The ionomer / nanoparticle dispersion was mixed for 20 minutes. The ionomer / nanoparticle dispersion was coated onto an unprimed PET substrate film in a continuous roll-to-roll process in which the dispersion was metered through a slot die onto a moving web. The ionomer / nanoparticle dispersion was metered by a metering pump and mass flow meter. The volumetric flow rate of each ionomer / nanoparticle dispersion was 73.8 cc / min. The volatile components of the coating formulation (i.e., the ionomer / nanoparticle dispersion) were removed in a three-zone air flotation oven. The temperatures of each zone, from oven entrance to exit, were 65.6°C, 79.4°C, and 135°C, respectively, and each oven section had a nominal length of 3.05 m. Table 3 shows the characterization results for an ionic elastomer nanocomposite coating (Preparative Example 6) with a coating thickness of 9.0 micrometers, a visible transmittance of 93%, and a haze of less than 1%. Note that the optical characterization includes the PET substrate and coating. The PET substrate was nominally 75 micrometers thick and had a transmittance of 91.5%, a haze of 0.65%, and a clarity of 99.9%. [Table 39]

[0136] Example 1: Ionic Elastomer Nanocomposite Film 37.5 grams of SURLYN 9120 were placed in a preheated Plasti-corder (CW Brabender Instruments, Inc., South Hackensack, NJ) and melted at 150°C and 75 rpm. 12.5 grams of the ionic elastomer nanocomposite coating (Preparation Example 6) was removed from the PET substrate and added to the Plasti-corder, and the contents were compounded for 15 minutes at 150°C and 75 rpm. After compounding, the nanocomposite was pressed into a film using an Auto Series hot press (Carver Inc., Wabash, IN). In the hot-pressing process, a portion of the compounded material was placed between polyimide sheets and then between polished aluminum plates. The nanocomposite was pressed into a film using a two-stage hot-pressing process. First, the nanocomposite was pressed at 900 kilograms force at 125°C and held for 5 minutes. In the second stage, the press automatically increased the pressure to 10,900 kilograms force at the same temperature, held for 0.1 minutes, after which the press automatically opened. The pressed film was removed from between the aluminum sheets and allowed to cool to room temperature before removing the polyimide sheet. A portion of the pressed film was pressed again using the same two-stage hot pressing process. Table 4 shows the characterization results for the ionic elastomer nanocomposite film (Preparation Example 7). The film exhibited a transmittance of 93.4% and a haze of 3.2%. TGA was used to measure the nanoparticle concentration in the nanocomposite film. The TGA result of 13.43 wt% correlates well with the calculated nanoparticle concentration of 10 wt%. Note that metal ions increase the TGA results. [Table 40]

[0137] Hypothetical Example 1: Ionic Elastomer Nanocomposite Hypothetical Example 1 illustrates the continuous compounding of an ionic elastomer nanocomposite. An 18 mm twin-screw extruder (Leistritz Extrisiontechnik GmbH, Nuremberg, Germany) is heated with the following temperature profile: Zone 1 = 260°C, Zones 2 and 3 = 265°C, Zones 4-6 = 268°C, and Zones 7 and 8 = 271°C. The ionic elastomer nanocomposite coating (Preparation Example 6) is removed from the PET substrate and fed into the extruder at a rate of 2.0 kg / hr. SURLYN 9120 is fed into the same extruder at a rate of 6 kg / hr. A strand die is attached to the end of the extruder. The extrudate, in the form of strands, is passed through a water bath at the end, which is a pelletizer that cuts the ionic elastomer nanocomposite into pellets.

[0138] Hypothetical Example 2: Multilayer Cast Web Hypothetical Example 2 illustrates a coextruded five-layer A:B:A:B:A cast web in which the center and two outer A layers are a thermoplastic such as PET, and the two inner B layers are an ionic elastomer nanocomposite. PET is extruded in a 25 mm twin-screw extruder (Leistritz Extrisonik GmbH, Nuremberg, Germany) with the following temperature profile: Zone 1 = 232°C, Zone 2 = 246°C, Zone 3 = 254°C, Zone 4 = 260°C, Zone 5 = 265°C. An ionic elastomer nanocomposite in pellet form (Hypothetical Example 1) is extruded in an 18 mm twin-screw extruder (Leistritz Extrisonik GmbH, Nuremberg, Germany) with the following temperature profile: Zone 1 = 260°C, Zones 2 and 3 = 265°C, Zones 4-6 = 268°C, and Zones 7 and 8 = 271°C. The two extruders feed into a feedblock designed to produce a five-layer A:B:A:B:A layer structure, with the die at 271°C. The multilayer extrudate is cast onto a chill roll with the aid of electrostatic pinning and wound onto a winder. The feed rate and casting wheel speed are adjusted to achieve a cast web thickness of nominally 500 to 2000 micrometers.

[0139] Hypothetical Example 3: Oriented Multilayer Film A 100 mm x 100 mm piece of the five-layer cast web of Hypothetical Example 2 is oriented using a KARO IV laboratory batch orienter (Bruckner Maschinenbau GMbH & Co KG, Siegsdorf, Germany). The cast web is loaded into the orienter. The cast web is preheated for 1 minute at a stretching temperature of 95-120°C. The cast web is stretched at a rate of 20% / sec. The stretch ratios are 2.5 x 2.5 and 4.0 x 4.0 (MD x TD). The oriented film has a thickness of 31 to 162 micrometers. Based on the above discussion, it is clear that a continuous roll-to-roll film of a desired thickness can be made in a process in which a thick multilayer film is cast and then oriented in a tenter to produce a roll of film having a thickness of, for example, 150 μm.

[0140] Hypothetical Example 4: Oriented Multilayer Film with Coating A roll of oriented multilayer film (Hypothetical Example 3) having a thickness of 150 μm is coated with an ionic elastomer dispersion (Preparation 3). 1319 grams of the ionic elastomer dispersion (Preparation Example 3) is placed in a clear glass jar. A Teflon-coated stir bar is added to the jar. The jar is placed on a stir plate and stirring is initiated. 431 grams of the silica nanoparticle dispersion (Preparation Example 5) is added to the jar. The ionomer / nanoparticle dispersion is mixed for 20 minutes. The ionomer / nanoparticle dispersion is coated onto an unprimed PET substrate film in a continuous roll-to-roll process in which the dispersion is metered through a slot die onto a moving web. The ionomer / nanoparticle dispersion is metered by a metering pump and mass flow meter. The volumetric flow rate of each ionomer / nanoparticle dispersion is 73.8 cc / min. Volatile components of the coating formulation (ionomer / nanoparticle dispersion) are removed in a three-zone air flotation oven. The temperatures in each zone are 65.6°C, 79.4°C, and 135°C, respectively, from oven entrance to exit, and each oven section has a nominal length of 3.05 m.

[0141] Hypothetical Example 5: Multilayer Film Article The coated article of Hypothetical Example 4 was laminated to glass. A first 15 cm x 15 cm layer of soda-lime glass was provided, approximately 3 mm thick. A few drops of deionized water were placed on the glass to wet the SURLYN 9120 nanocomposite ionomer layer to the glass. A squeegee was used to squeeze out excess DI water between the glass and the ionomer film. The film was allowed to rest at room temperature for approximately 1 hour and then placed in a 70°C oven to bond the ionomer film to the glass. The ionomer-glass composite structure was removed from the oven and allowed to cool, providing a multilayer film article bonded to the glass.

[0142] Hypothetical Example 6: Multilayer Film Article A multilayer optical film is produced by coextrusion of 224 alternating layers of PET and coPMMA with a cast web thickness of approximately 580 μm. An ionic elastomer nanocomposite (Hypothetical Example 1) is coextruded as an outer layer on both sides of the PET:coPMMA optical stack. Each of the outer ionic elastomer nanocomposite layers is approximately 1500 μm thick. The cast web is preheated and stretched in the machine direction (MD) at approximately 90°C at a ratio of 3.7:1, and then stretched in the transverse direction (TD) at approximately 100°C at a ratio of 3.9:1 to produce an approximately 248 μm thick film with each ionic elastomer nanocomposite layer being 104 μm thick and the optical stack being 40 μm thick.

[0143] A two-glass layer structure with a glass layer bonded together with a multilayer optical film was fabricated using the following process: A first 15 cm x 15 cm layer of soda-lime glass was prepared, approximately 3 mm thick. A few drops of deionized water were placed on the glass to wet one side of the multilayer optical film bearing the ionic elastomer skin to the glass. A squeegee was used to squeeze out excess DI water between the glass and the nanocomposite layer. The film was allowed to rest at room temperature for approximately 1 hour. The exposed ionic elastomer skin layer was then bonded to a second 15 cm x 15 cm layer of soda-lime glass. Deionized water was placed in the center of the second glass layer, and the ionic elastomer skin attached to the first glass layer was carefully placed in contact with the water, allowing for nearly airless contact between the ionic elastomer skin layer and the second glass layer. The entire glass structure was allowed to rest for 1 hour. The glass assembly is then placed in an autoclave at 70°C and pressurized to bond the ionic elastomer nanocomposite layer to the glass layer and remove air. After a sufficient time, the glass assembly is removed from the autoclave, resulting in a two-layer glass composite assembly.

[0144] Terms such as "about" will be understood by those of ordinary skill in the art in the context in which they are used and described herein. Where the use of "about" as applied to quantities expressing feature sizes, amounts, and physical characteristics is not clear to those of ordinary skill in the art in the context in which it is used and described herein, "about" will be understood to mean within 10 percent of a particular value. A quantity given as about a particular value may be exactly that particular value. For example, where it is not clear to those of ordinary skill in the art in the context in which it is used and described herein, an amount having a value of about 1 means that the amount has a value between 0.9 and 1.1, and may be 1.

[0145] All of the above-referenced references, patents, or patent applications are hereby incorporated by reference in their entirety. In the event of any inconsistency or contradiction between the incorporated reference portions and this application, the information in the foregoing description shall prevail.

[0146] Descriptions of elements in a figure should be understood to apply equally to corresponding elements in other figures unless otherwise indicated. While specific embodiments have been illustrated and described herein, those skilled in the art will recognize that the specific embodiments illustrated and described may be replaced by various alternative and / or equivalent embodiments without departing from the scope of the present disclosure. This application is intended to cover any adaptations, or variations, or combinations of the specific embodiments discussed herein. Accordingly, the present disclosure is intended to be limited only by the claims and equivalents thereof.

Claims

1. 1. A multilayer film comprising a plurality of first layers and a polymeric second layer disposed along a thickness of the multilayer film, the first and second layers having different compositions, each of the first layers comprising: at least one polymer, the at least one polymer comprising a first polymer comprising (meth)acrylic acid monomer units; Dispersed in the at least one polymer are metal oxide nanoparticles having Formula 1: 【Chemistry 1】 [In the formula, R1 is C 1 ~C 10 is an alkoxy group, R2 and R3 are independently C 1 ~C 10 Alkyl group and C 1 ~C 10 alkoxy groups; A is C 1 ~C 10 an alkylene group or an arylene group, C 1 ~C 10 Aralkylene group, C 2 ~C 16 a heteroalkylene group or a heteroarylene group, and C 2 ~C 16 and metal oxide nanoparticles that have been surface-modified with a surface modifier comprising a carboxylic acid silane of the formula (I), wherein the linker group is selected from the group consisting of amide-containing groups.

2. 10. The multilayer film of claim 1, wherein each second layer comprises a polyester comprising terephthalate monomer units and ethylene glycol monomer units.

3. 10. The multilayer film of claim 1, wherein each of the first and second layers has an average thickness of less than 500 nm, and the number of the first and second layers totals at least 50.

4. 4. The multilayer film of claim 3, which is a visible light mirror film, an infrared mirror film, a reflective polarizer, or a notch optical filter.

5. 10. The multilayer film of claim 1, having a light transmission of at least 80 percent for unpolarized light at substantially normal incidence.

6. The multilayer film of claim 1 , wherein the first and second layers alternate along the thickness direction.

7. 10. The multilayer film of claim 1, further comprising a plurality of third layers of polymer disposed along the thickness direction with the first and second layers.

8. The multilayer film of claim 1 , further comprising a plurality of alternating polymer layers disposed on said plurality of first and second layers.

9. 9. The multilayer film of claim 8, having an average light transmittance of at least 70 percent for unpolarized light at substantially normal incidence over a wavelength range extending from at least 450 nm to 650 nm, and an average light transmittance of no more than 50% for unpolarized light at substantially normal incidence over a wavelength range extending from at least 900 nm to 1000 nm.

10. 10. The multilayer film of claim 1, wherein the at least one polymer further comprises a second polymer different from the first polymer blended with the first polymer, the second polymer comprising (meth)acrylic acid monomer units.

11. An optical stack comprising a glass layer and the multilayer film of any one of claims 1 to 10 disposed on the glass layer.

12. 1. A multilayer film comprising a first layer and a plurality of alternating polymer layers disposed on the first layer, the first layer comprising: at least one polymer, the at least one polymer comprising a first polymer comprising (meth)acrylic acid monomer units; Dispersed in the at least one polymer are metal oxide nanoparticles having Formula 1: 【Chemistry 2】 [In the formula, R1 is C 1 ~C 10 is an alkoxy group, R2 and R3 are independently C 1 ~C 10 Alkyl group and C 1 ~C 10 alkoxy groups; A is C 1 ~C 10 an alkylene group or an arylene group, C 1 ~C 10 Aralkylene group, C 2 ~C 16 a heteroalkylene group or a heteroarylene group, and C 2 ~C 16 and metal oxide nanoparticles that have been surface-modified with a surface modifier comprising a carboxylic acid silane of the formula (I), wherein the linker group is selected from the group consisting of amide-containing groups.

13. 13. The multilayer film of claim 12, further comprising a second layer and at least one subgroup of the plurality of alternating polymer layers disposed between the first and second layers, the second layer comprising at least one polymer, and the at least one polymer of the second layer comprising a first polymer comprising (meth)acrylic acid monomer units.

14. 14. The multilayer film of claim 13, wherein the second layer further comprises metal oxide nanoparticles dispersed in the at least one polymer of the second layer, and the metal oxide nanoparticles of the second layer are surface modified with a carboxylic acid silane surface modifier.

15. 13. The multilayer film of claim 12, wherein the alternating polymer layers comprise alternating first and second interference layers, each first interference layer comprising at least one polymer, the at least one polymer of the first interference layer comprising a polymer comprising (meth)acrylic acid monomer units, and each second interference layer comprising an oriented polyester.